If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 87 = -3(4x + -5) Reorder the terms: 87 = -3(-5 + 4x) 87 = (-5 * -3 + 4x * -3) 87 = (15 + -12x) Solving 87 = 15 + -12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12x' to each side of the equation. 87 + 12x = 15 + -12x + 12x Combine like terms: -12x + 12x = 0 87 + 12x = 15 + 0 87 + 12x = 15 Add '-87' to each side of the equation. 87 + -87 + 12x = 15 + -87 Combine like terms: 87 + -87 = 0 0 + 12x = 15 + -87 12x = 15 + -87 Combine like terms: 15 + -87 = -72 12x = -72 Divide each side by '12'. x = -6 Simplifying x = -6
| -85=-5(3+7r) | | -3(-6+4r)=90 | | -8(2v+6)=-96 | | 5=-10+a | | 5=10+a | | R+6=25 | | 35-x^7=53+x^3 | | Whatisf(x)whenx=2.4 | | 90x=306 | | 2/3-4=-2 | | 8x-3(x+6)=x+14 | | 293-y=131 | | 75+7x=180 | | 2x+10+5x=3 | | 107+4x+15=180 | | 4x+5=107 | | 7y+7=4+2y | | 8(2x-5)+11x= | | X^2-xy-2y^2=(x+y)(x-2y) | | 5/12/3/16 | | 6x-8y=9x+10y-1z | | -3x/4x=21 | | -4.8/6.6 | | 6=2(w-7)-4w | | 5x+4(2x*10)=1 | | 15ab-4a+5b= | | 6x+7-3x=8x-13 | | 39=0.5(-12n+30) | | 4+3[6x-4(5+2x)]= | | 2x+26=146+2x+172 | | (4x+4y)x(4x-4y)= | | h=-16t^2+110t+6 |